Case Report - Anterior Open Bite as a Complication of Splint Therapy - Todd M.A; Freer T.J (Sciendo, 1994)
A case of anterior open bite secondary to occlusal splint therapy in the adult is described. The occlusal splint covered all maxillary teeth, including the third molars. A brief discussion of the findings and treatment considerations is presented.